Relationship Between Leadership Styles, Organizational Commitments and Motivational Factors Towards Organizational Performance and Employee Turnover Intention (Journal of Asian Development Studies, 2026)
This study examined the relationship between leadership styles, organizational commitment, motivational factors, organizational performance, and employee turnover intention in public and private sector health organizations. A descriptive cross-sectional design was employed, with a sample of 450 employees selected through simple random sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using SPSS version 22 and Structural Equation Modeling (SEM). The findings revealed that leadership styles significantly and positively influence organizational commitment, indicating that effective leadershipenhances employees’ attachment to their organization. Motivational factors, particularly rewards and recognition, were also found to be strong predictors of organizational commitment and performance. Among the dimensions of commitment, continuance and normative commitment showed significant positive effects, whereas affective commitment did not demonstrate a significant relationship in the model. Furthermore, organizational commitment was positively associated with organizational performance and negativelyassociated with employee turnover intention, suggesting that committed employees are more productive and less likely to leave their organization. Job satisfaction did not show a significant direct effect on organizational commitment, indicating its potential role as a mediating factor. The model fit indices confirmed that the proposed conceptual framework was statistically sound and adequately represented the relationships among the study variables. Overall, the study highlights the critical role of leadership and motivation in fostering organizational commitment, improving performance, and reducing turnover intention. These findings provide valuable insights for policymakers and organizational leaders aiming to enhance workforce stability and effectivenessin healthcare and public sector settings.